PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI TAMAN PUTRI TUNGGAL KABUPATEN KERINCI - Ayu Lestari, Anggia (STIE Mahardhika, 2025)
This study aims to analyze and explain the significant impact of the marketing mix on tourist decisions to visit Taman Putri Tunggal, Kerinci district. The variables of this study include product, place, price and promotion on tourist interest. The population is all tourists who visit Taman Putri Tunggal. A sample of 100 respondents was selected to represent this population. Multiple regression analysis with SPSS 16.0 was used to test the hypotheses. The findings prove that factors such as the types of tours offered, ticket prices, location, and promotion strongly influence tourists' decision to visit Taman Putri Tunggal. However, this study only focused on one tourist attraction, so further research with a focus on a different tourist attraction is needed.